A sensitive electrochemical sensor modified with multi‐walled carbon nanotubes doped molecularly imprinted silica nanospheres for detecting chlorpyrifos. Issue 5 (27th December 2019) - Huang, Weihong; Zhou, Xiaohua; Luan, Yu; Cao, Yunfei; Wang, Ningwei; Lu, Yi; Liu, Tianshu; Xu, Wanzhen
Abstract: A highly sensitive and convenient electrochemical sensor, based on surface molecularly imprinted polymers and multiwalled carbon nanotubes, was successfully developed to detect chlorpyrifos in real samples. In order to solve the problems like uneven shapes, poor size accessibility, and low imprinting capacity, the layer of the molecularly imprinted polymer was prepared on the surface of silica nanospheres. Moreover, the doping of multiwalled carbon nanotubes greatly improved the electrical properties of developed sensor. Under the optimal conductions, the electrochemical response of the sensor is linearly proportional to the concentration of chlorpyrifos in the range of 5.0 × 10 −12 ‐5.0 × 10 −8 mol/L with a low detection limit of 8.1 × 10 −13 mol/L. The prepared sensor exhibited multiple advantages such as low cost, simple preparation, convenient use, excellent selectivity, and good reproducibility. Finally, the prepared sensor was successfully used to detect chlorpyrifos in vegetable and fruit.